Acceptance of Fate in Stoicism: A Philosophical Review of the Phenomenon of Students in the Wrong Major - Ahmad Farid Fanani; Novian Widiadharma (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
The phenomenon of students pursuing the wrong major is a prevalent issue in higher education, yet it remains minimally explored from a philosophical perspective. This study aims to explore the experiences of students who feel mismatched with their major through the lens of Stoic philosophy, particularly focusing on aspects of feelings, attitudes, and actions concerning fate. This research employs a philosophical inquiry approach. Data were obtained through in-depth interviews and analyzed using the Stoic theory of fate acceptance, which encompasses feelings, attitudes, and actions. The findings indicate that students in misaligned majors were able to reflect on their experiences in a Stoic manner by managing negative emotions, accepting reality as an optimal part of fate, and undertaking rational and prudent actions in their academic pursuits and future trajectory. This finding suggests that Stoicism can be a relevant approach to addressing the psychological dynamics of university students. This study contributes to the development of reflective approaches in academic advising and enriches the discourse of practical philosophy in higher education.